1990
DOI: 10.1002/1097-0142(19900201)65:3<481::aid-cncr2820650318>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal regulation of coagulation/fibrinolysis in small cell carcinoma of the lung

Abstract: Components of coagulation and fibrinolysis reactions were identified in situ by immunohistochemical staining in fresh frozen sections of small cell carcinoma of the lung tissue. Tumor cells stained positively for tissue factor, a protein that is capable of activating the extrinsic pathway of coagulation (the components of which have been seen within small cell carcinoma of the lung [SCCL] tissue), and for proteins C and S antigens. Fibrin was seen in a focal distribution at the host-tumor interface, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 28 publications
3
71
0
Order By: Relevance
“…We have shown absent or negligible procoagulant activity in a panel of SCLC cell lines (Keller et al 2001). Reports on TF expression in SCLC tumour specimens are rare (Wojtukiewicz et al 1990) and not conclusive probably since SCLC is rarely resected and only limited numbers of specimens are available.…”
Section: Introductionmentioning
confidence: 62%
“…We have shown absent or negligible procoagulant activity in a panel of SCLC cell lines (Keller et al 2001). Reports on TF expression in SCLC tumour specimens are rare (Wojtukiewicz et al 1990) and not conclusive probably since SCLC is rarely resected and only limited numbers of specimens are available.…”
Section: Introductionmentioning
confidence: 62%
“…Fibrin may also promote angiogenesis. The fibrin clot and the associated coagulation factors provide a highly pro-angiogenic environment [24] Previous studies documented the presence of fibrin and fibrinogen in situ in small cell carcinoma of the lung, renal cell carcinoma, malignant melanoma, and ovarian carcinoma [25][26][27][28][29][30][31]. In this study it was found that beta fibrin was 2.77 fold increased in abundance levels in the saliva from the patients with HNSCC compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated thrombinantithrombin HI levels are consistent with an earlier study on this topic, in which thrombin-antithrombin III was considered a marker of malignant gynaecological disease (17). In general, an explanation for the activation of blood coagulation in tumours is thought to be a direct interaction of the coagulation factors with tumour cells (18,19) or an indirect production of cytokines (20). The evidence for both of these etiologies are however based on immunohistological investigations.…”
Section: Discussionmentioning
confidence: 99%